Finite Element Analysis on Contact Pressure and 3D Breast Deformation for Application in Women’s Bras - Sun, Yue; Yick, Kit-lun; Cai, Yiqing; Yu, Winnie; Chen, Lihua; Lau, Newman; Zhang, Shichen (Fibers and polymers, 2021)
A well-fitting bra provides adequate and exceptional support of the breasts and the desirable body shape for the wearer but would not exert excessive pressure onto the breasts. Among the different design features of bras, the materials selected for the bra cups are a key element for enhancing breast support and improving the perceived comfort. This paper proposes a subject-specific model based on numerical simulation to investigate the influence of different types of bra cup materials on the shape of the breasts and amount of pressure on the breasts. The study comprises three phases. The first phase is the development of a subject-specific contact model and simulation of the bra-wearing process. The second phase is the construction and analysis of three models with different bra cup materials (knitted, woven and foam) to compare their shaping effects on the breasts and the corresponding amount of applied contact pressure. The third phase uses the validated numerical model to simulate the use of a series of virtual bra cup materials, their impact on the shape of the breasts, and the associated bra pressure. It is found that a stiffer fabric has a better performance in reshaping the breasts and reducing the amount of pressure from the straps onto the neck for a halter-neck bra but distributes a higher amount of pressure at the bottom part of the breasts. An overall better performance of reshaping the breasts is achieved by increasing the tensile strength of the bra cup material. Nevertheless, the small change in the shaping effects can be negligible after the Young’s modulus reaches about 1.5 MPa. Among the four measured variables, it is more useful to measure the gathering of the breasts and depth of cleavage than the lifting of the breasts to determine the amount of breast deformation caused by a bra. The newly developed finite element model for contact analysis in this study provides a better understanding on the interactive process between the breasts and the bra by predicting the deformation within a variance of 6.8 % in comparison to the experimental results of the contact pressure with the same trend and magnitude. Numerical simulations can therefore facilitate decisions on the type of fabric used for bra designs that provide optimal fabric pressure and other stretchable apparel products that take both the shaping effect and wear comfort into consideration.